Perbedaan Kinerja Guru Bimbingan dan Konseling dalam Menyelenggarakan Konseling Individual Ditinjau dari Latar Belakang Pendidikan dan Pengalaman Bekerja - Barida, Muya; Muarifah, Alif (Jurnal Kajian Bimbingan dan Konseling, 2019)
The particular study aimed to determine the differences performance between school counselors in organizing individual counseling services in schools in terms of educational background and work experience. The research approach was descriptive survey through a descriptive comparative study design. The subjects were school counselor in Daerah Istimewa Yogyakarta, especially at Bantul Regency. The data analysis technique used two way ANOVA. Based on the statistical tests, the educational background and work experience did not significantly affect the performance of school counselors in providing individual counseling services in schools.